2022
DOI: 10.1371/journal.pone.0269429
|View full text |Cite
|
Sign up to set email alerts
|

I love the way you love me: Responding to partner’s love language preferences boosts satisfaction in romantic heterosexual couples

Abstract: Chapman’s Love Languages hypothesis claims that (1) people vary in the ways they prefer to receive and express affection and (2) romantic partners who communicate their feelings congruent with their partner’s preferences experience greater relationship quality. The author proposes five distinct preferences and tendencies for expressing love, including: Acts of Service, Physical Touch, Words of Affirmation, Quality Time and Gifts. In the present study partners (N = 100 heterosexual couples) completed measures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Secondly, having sex for love and commitment reasons was associated with better psychological health QoL, which is in line with studies by Brunell and Webster [ 48 ] who found that love and commitment in romantic relationships are linked to better sexual satisfaction and psychological health. Accordingly, Mostova, Stolarski, and Matthews [ 49 ] found that expressing and receiving love in preferred ways, such as physical touch, can increase sexual satisfaction and overall psychological well-being [ 50 ]. Muise and Impett also found that those with higher communal strength, that is people who are motivated to respond unconditionally to their partners’ sexual requirement, are more likely to satisfy their partner’s sexual needs, leading to increased relationship and psychological well-being [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, having sex for love and commitment reasons was associated with better psychological health QoL, which is in line with studies by Brunell and Webster [ 48 ] who found that love and commitment in romantic relationships are linked to better sexual satisfaction and psychological health. Accordingly, Mostova, Stolarski, and Matthews [ 49 ] found that expressing and receiving love in preferred ways, such as physical touch, can increase sexual satisfaction and overall psychological well-being [ 50 ]. Muise and Impett also found that those with higher communal strength, that is people who are motivated to respond unconditionally to their partners’ sexual requirement, are more likely to satisfy their partner’s sexual needs, leading to increased relationship and psychological well-being [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is only a limited body of empirical research on love languages, the work that does exist does not provide strong support for the validity of the love languages’ core assumptions. First, contradicting the notion that “we speak only our primary language” (Chapman, 2015, p. 15), studies have consistently demonstrated that people tend to endorse all five love languages as meaningful ways of expressing love and feeling loved (Bunt & Hazelwood, 2017; Cook et al, 2013; Egbert & Polk, 2006; Mostova et al, 2022; Polk & Egbert, 2013; Surijah et al, 2020). Specifically, the ratings on the Likert-type measures consistently exhibit highly skewed distributions, with most ratings falling above the midpoint of the scale and average ratings hovering around 4 on a 5-point scale for all five love languages.…”
Section: Empirical Review Of the Love Languagesmentioning
confidence: 99%
“…Consequently, studies have shown that a person’s primary love language, as identified by the forced-choice LLPP measure, is not reliably associated with their scores on the continuous measure (Mostova et al, 2022; Polk & Egbert, 2013; Surijah et al, 2020), such that a person’s forced-choice primary love language does not surface as their highest-rated love language on the continuous measure. For example, Polk and Egbert (2013) found that a majority of their sample were categorized as having quality time or physical touch as their primary love language when using the forced-choice measure, but gifts showed the highest mean score using the Likert-type measure.…”
Section: Empirical Review Of the Love Languagesmentioning
confidence: 99%
See 2 more Smart Citations